Clozapine- and non-clozapine-associated neutropenia in patients with schizophrenia: a retrospective cohort study. (March 2022) - Johannsen, Claas-Frederik; Petersen, Tonny Studsgaard; Nielsen, Jimmi; Jørgensen, Anders; Jimenez-Solem, Espen; Fink-Jensen, Anders
Introduction: The antipsychotic drug clozapine remains underutilized partly because of the risk of life-threatening adverse effects, such as neutropenia. Therefore, an extensive hematological monitoring program was set up to detect neutropenia. Methods: In this retrospective cohort study, we used registry-based data from the Capital Region of Denmark to investigate incidence rates of neutropenia among patients with a diagnosis of schizophrenia or other psychotic disorders and treated with clozapine for the first time. In a within-subject design, we compared rates of neutropenia in time periods where patients were exposed to clozapine versus time periods, where they were not exposed to clozapine. We also investigated whether the lengths of clozapine-associated neutropenia (CAN) were related to discontinuation of clozapine treatment. Results: Data from 520 clozapine users were included. The incidence rate of CAN was 3.2 cases per 100 person-years (95% confidence interval [CI]: 2.1–4.8) throughout the entire study. There was no significant difference in incidence rates of neutropenia during clozapine exposure and non-clozapine exposure, with an incidence rate ratio of 0.7 (95% CI: 0.4–1.3). One episode of severe neutropenia was detected. Episodes of CAN with only one sub-threshold neutrophil count were not associated with higher clozapine discontinuation (26%) than CAN episodes of more than one sub-threshold neutrophil count (28%). Conclusion: In the present study, we could not confirm that clozapine treatment was associated with neutropenia.